Global Robotics Competition Meets Inclusive Education: The Exceptional Journey of Five Resilient Students - Simon Parent; Sara Iatauro (LEARNing Landscapes, 2019)
The 2018 edition of RoboCup allowed young people from Centre de formation en entreprise et récupération (CFER) de Bellechasse to demonstrate their skills in programming and robotics. In this school, as in many schools, the use of technology is a particularly effective learning tool, especially for students facing challenges. The construction of a robotic device has allowed them to develop several skills, some of which can be reinvested in various contexts, whether at school or in their professional life. This commentary briefly presents the exceptional journey of Bellechasse students who were able to overcome many obstacles and compete with gifted students from around the world.